Different External Interference Directly Leads to Different Endings for Transgenders - Xiang Li (Studies in Social Science & Humanities, 2024)
Based on Judith Butler’s gender performativity theory, this paper reveals that the nature of gender is an idealized imitation and expression, which breaks the original binary opposition between heterosexuality and sexual minorities and analyzes the impact of symbolic society’s views of such imitative behavior as an inherent attribute of gender on sexual minorities. The protagonists in Kafka’s Metamorphosis and Alain Berliner’s movie My Life in Pink both reflect the living conditions of transgenders in real society. They face the same dilemma but have completely different endings. Due to the different reactions of the external environment and people around them, the psychological changes and personality shaping of the two transgenders are also totally different, Gregor died tragically, but Ludovic was eventually accepted by society. Therefore, breaking the stereotyped thoughts of gender by combining gender performativity theory, this paper makes a comparative analysis of the influence from external interference on the personality shaping of transgenders in the two genres, calling for a more open and inclusive social environment.